IL-17C/IL-17RE: Emergence of a Unique Axis in TH17 Biology - Nies, Jasper F.; Panzer, Ulf (Frontiers in Immunology, 2020)
Therapeutic targeting of IL-17A and its receptor IL-17RA with antibodies has turned out to be a tremendous success in the treatment of several autoimmune conditions. As the IL-17 cytokine family consists of six members (IL-17A to F), it is intriguing to elucidate the biological function of these five other molecules to identify more potential targets. In the past decade, IL-17C has emerged as quite a unique member of this pro-inflammatory cytokine group. In contrast to the well described IL-17A and IL-17F, IL-17C is upregulated at very early timepoints of several disease settings. Also, the cellular source of the homodimeric cytokine differs from the other members of the family: Epithelial rather than hematopoietic cells were identified as the producers of IL-17C, while its receptor IL-17RE is expressed on TH17 cells as well as the epithelial cells themselves. Numerous investigations led to the current understanding that IL-17C (a) maintains an autocrine loop in the epithelium reinforcing innate immune barriers and (b) stimulates highly inflammatory TH17 cells. Functionally, the IL-17C/ RE axis has been described to be involved in the pathogenesis of several diseases ranging from infectious and autoimmune conditions to cancer development and progression. This body of evidence has paved the way for the first clinical trials attempting to neutralize IL-17C in patients. Here, we review the latest knowledge about identification, regulation, and function of the IL-17C / IL-17receptor E pathway in inflammation and immunity, with a focus on the mechanisms underlying tissue injury. We also discuss the rationale for the translation of these findings into new therapeutic approaches in patients with immune-mediated disease.